Comparative European Institutions and the Little Divergence, 1385-1800 - António Henriques; Nuno Palma (European Historical Economics Society (EHES), 2019)
Why did the countries which first benefitted from access to the New World - Castile and Portugal - decline relative to their followers, especially England and the Netherlands? The dominant narrative is that worse initial institutions at the time of the opening of Atlantic trade explain Iberian divergence. In this paper, we build a new dataset which allows for a comparison of institutional quality over time. We consider the frequency and nature of parliamentary meetings, the frequency and intensity of extraordinary taxation and coin debasement, and real interest spreads for public debt. We find no evidence that the political institutions of Iberia were worse until at least the English Civil War.
Keywords: N13; N23; O10; P14; P16; 330; Atlantic Traders; New Institutional Economics; The Little Divergence